Biochemical and behavioral deficits in the lobster cockroach Nauphoeta cinerea model of methylmercury exposure (2015)
Methylmercury (MeHg) is well-known for its neurodevelopmental effects both in animals and in humans. As an alternative to utilizing conventional animal models, this study evaluated behavioral and biochemical parameters using the nymphs of the lobster cockroach Nauphoeta cinerea. Animals were exposed to MeHg at 0, 0.03125, 0.0625, 0.125, 0.25 and 0.5 mg per g feed for 35 consecutive days. Locomotor activity and exploratory profiles were analyzed using video-tracking software during a 10 minute trial. Subsequently, biochemical estimations were carried out using cockroach heads. MeHg exposure caused behavioral impairment as evidenced by a significant decrease in distance travelled, time spent walking, turn angle and body rotation. The marked decrease in the exploratory profiles of MeHg-exposed cockroaches was confirmed by track plots, whereas occupancy plot analyses revealed a gradual dispersal in homebase formation, starting from 0.0625 mg per g feed. Biochemically, MeHg exposure significantly decreased acetylcholinesterase activity (AChE), an enzyme which plays a pivotal role in neurotransmission. Moreover, MeHg caused increased oxidative stress as evidenced by decreased total thiol levels and glutathione S-transferase (GST) activity, along with increased 2’,7’-dichlorofluorescein (DFCH) oxidation and thiobarbituric acid reactive substance (TBARS) production. In conclusion, these data demonstrated that Nauphoeta cinerea mimics the behavioral and biochemical deficits observed in rodents exposed to MeHg, thus highlighting its validity as an alternative model for basic toxicological studies.